Acibenzolar‐S‐methyl activates mitogen‐activated protein kinase cascade to mediate chlorophyll and carotenoid metabolisms in the exocarp of Docteur Jules Guyot pears. (10th February 2022) - Li, Canying; Zhu, Jie; Cheng, Yuan; Hou, Jiabao; Sun, Lei; Ge, Yonghong
Abstract: BACKGROUND: Acibenzolar‐ S ‐methyl (ASM), a well‐known plant activator, has been used to protect fruit and vegetable from fungal invasion and maintain quality. However, little is known about the molecular mechanism of ASM in regulating chlorophyll and carotenoid metabolisms. Therefore, Docteur Jules Guyot pears were used as the materials to study the changes of hydrogen peroxide (H2 O2 ) production, mitogen‐activated protein kinase (MAPK) cascade, transcription factors, chlorophyll, and carotenoid metabolisms after ASM and PD98059 (a MAPK cascade blocker) treatments. RESULTS: ASM increased NADPH oxidase (NOX) and superoxide dismutase (SOD) activities, and H2 O2 content, promoted PcMAPKKK1, PcMAPKK3, and PcMAPK6 expressions, and down‐regulated PcMYC2, PcPIF1, PcPIF3, and PcPIF4 expressions in exocarp of pears. ASM also delayed the decrease of chlorophyll a and b contents, and inhibited the accumulation of β‐carotene, lycopene and lutein, PcNYC1, PcHCAR, PcPPH, PcSGR1 /2, PcPAO, PcPSY, PcLCYB, PcCRTZ2, PcCCS1 expressions, and promoted PcLCYE expression. PD98059 + ASM treatments depressed SOD and NOX activities and H2 O2 content, inhibited PcMAPKKK1, PcMAPKK3, PcMAPK6, PcPIF1, and PcPIF3 expressions, and promoted PcMYC2 and PcPIF4 expressions in exocarp of pears. Additionally, PD98059 + ASM accelerated PcNYC1, PcHCAR, PcPPH, PcSGR1 /2, PcPAO, PcPSY, PcCYB, PcCRTZ2, and PcCCS1 expressions, thereby reducing chlorophyll a and b contents, and promoting β‐carotene, lycopene and lutein contents. CONCLUSIONS: Postharvest ASM treatment promoted the production of H2 O2 to activate the MAPK cascade, then phosphorylated/dephosphorylated transcription factors expression, and delayed chlorophyll decomposition and carotenoid synthesis in pears. © 2022 Society of Chemical Industry.